Data for: Determining the minimum detectable activity of coincidence HPGe gamma-ray spectrometers using simulation tools - Arnqvist, Elias; Jansson, Peter; Andersson, Peter; Dar, Shabir (Uppsala University, 2026)
Measured and simulated data for HPGe coincidence gamma spectrometers are provided in this dataset. Measured list-mode and spectrum data are provided for a shielded and an unshielded background environment, in addition to calibration data. For simulated data, both uncompiled Geant4 applications and their output data are provided. Simulated detector response functions, background spectra, and a detector design optimization example are included. The SURE background model is implemented in Geant4 in each case.

Data is primarily in .root or .n42 format. ROOT (6.34.04) can be used to open .root files. InterSpec (1.0.13) can be used to open .n42 files. Geant4 applications can be compiled with the Geant4 toolkit (11.3.2). Python scripts can be run with Python (3.13.3).

Uppmätt och simulerad data för HPGe-koincidensgammaspektrometrar är tillgängliga i det här datasetet. Uppmätt listformaterad och spektrumformaterad data är tillgängliga för en skärmad och oskärmad bakgrundsmiljö, tillsammans med kalibreringsdata. För simulerad data är både okompilerade Geant4-applikationer och deras utdata tillgängliga. Simulerade detektorresponsfunktioner, bakgrundsspektra och ett exempel på optimering av detektordesign är inkluderade. Den så kallade SURE bakgrundsmodellen är implementerad i Geant4 i varje fall.

Data är primärt i .root- eller .n42-format. ROOT (6.34.04) kan användas för att öppna .root-filer. InterSpec (1.0.13) kan användas för att öppna .n42-filer. Geant4-applikationer kan kompileras med Geant4-toolkitet (11.3.2). Python-skript kan köras med Python (3.13.3).
Data för: Determining the minimum detectable activity of coincidence HPGe gamma-ray spectrometers using simulation tools
Keywords: HPGe; HPGe; gamma spectrometry; gammaspektrometri; Geant4; Geant4; coincidence measurements; koincidensmätningar; Subatomic Physics; Subatomär fysik; Engineering and Technology; Teknik